Corporate Branding in Online Startups - Fojtíková, Pavlína (2014)
The purpose of this Master's thesis is to explore corporate branding in online startups from the entrepreneurial perspective. In total, nine companies -- mostly Czech and German-based Internet startups - were researched. The principal method employed is the qualitative research based on in-depth interviews with startup founders and managers. The thesis shows that the literature on corporate branding mostly coincides with the reality of online startups, reveals that there is no consensus about the importance of corporate branding among startup representatives and explains the corporate brand building practices in online startups. In conclusion, recommendations for prospective entrepreneurs are proposed.